O SAGRADO E O PROFANO NA EDUCAÇÃO: um estudo do imaginário religioso na escola pública - Cavalcanti, Alberes de Siqueira (2007)
This work is a quality research about the religious imaginary on the public education. The categories of conception are sacred and profane. The mean proposals are to define the process of secularization in the occidental culture, its reflections on the school universe, the comprehension of the religious imaginary of the school community and the images and symbols mapping found at the public school. The study was carried out at two municipal schools in São Luís. The data survey about the researched public was made through open questionnaire, drawing and text. Besides, were included the observation in loco and pictures of the place. The research is based on the studies of Mircea Eliade and Gilbert Durand and shows the sacred and profane representations on the symbolic universe of schools and how they reflects on the pedagogical work. The study shows up the religious imaginary there observed characterized for day images and Jewish-Christian symbolism, all through survey and interpretation of the school space-time symbolism. The events carried out at the school stand out as rituals geared toward the school microcosm establishment. The survey shows the interpretation of the school from its symbolism onwards as sacred space-time devoted to the knowledge and discipline in a moving ritual of students to the social life. The work reveals the image of a heroic and redeeming school by the relation of images of ascension, illumination and separation.